Avaliação da inclusão da glicerina bruta na água de ovelhas lactantes - Felipe Santiago Santos (2016)
Crude Glycerin (CG) in water demonstrated a potential for use in diet of dairy sheep. The Recent politics of renewable energy have promoted a surplus of CG. This product can be applied into ruminant nutrition, as a cheap source of energy, of easy storage and supplying, which can replace traditional foods such as corn, wheat and rice meal, commonly used in the sheep industry. The objective was to evaluate the effects of the inclusion of glycerin in water for dairy sheep on nutrient intake, milk yield and composition, as well as glycemic parameters promoted by supplementation. Twenty dairy ewes, initial weight 62.68 ± 5.95 kg, were distributed in a completely randomized design, in four treatments differed as to supplementary CG diluted in water: zero, 1.5%, 3, 0% to 4.5% of dry matter intake. There was a linear decrease (P<0.05) of dry matter intake and milk yield. Milk yield was corrected to 6.5% fat and 5.8% protein. Concentration of lactose and milk protein were increased linearly with the inclusion of Glycerin (P <0.05); however, urea concentration in milk reduced quadratically (P <0.05). There was no effect on feed conversion ratio (P> 0.05). The increased inclusion of CG linearly improved the efficiency of the use of nitrogen in the milk yield (P <0,05). The deleterious effects on dry matter intake and milk production may be compensated as an improvement in diet efficiency.